Navigating Challenges in EFL Writing: A Case Study on Technology Integration in Online Classrooms - Hapsari, Christianti Tri; Anjaniputra, Agung Ginanjar (Jurnal Bahasa dan Sastra, 2025)
Teachers and educators have prioritized technological integration. Despite its necessity, it can cause many context-specific concerns for teachers and students, which differ from those caused by the rapid development of the Internet of Things. Additionally, few studies exist on writing skills. This study aims to portray emerging problems in integrating digital media into the classroom, particularly in EFL writing. The data were collected by involving an English teacher under the umbrella of qualitative research with a case study design. The research instruments comprise a semi-structured interview, a questionnaire, and classroom observation, all of which are then triangulated. The findings showed that the teacher’s barriers concerning certain aspects of incorporating technology were related to Relative Advantage, Compatibility, Complexity, Observability, and Faultability. The unique focus of this study is faultability, that is, the way technical limitations in the use of technology impact teacher performance. Thus, the integration of online media in teaching writing must consider automatic saving, history, and demonstration. It is suggested that stakeholders facilitate teachers’ concerns regarding the use of technology in the classrooms and that teachers utilize technology not only to replace non-digital media but also to optimally enhance students’ writing skills. The contribution of this study lies in how the specific challenges faced by teachers in using online media for writing can offer practical insights for teachers and policymakers to improve the effectiveness of technology-supported pedagogy.